2020
DOI: 10.1155/2020/1467403
|View full text |Cite
|
Sign up to set email alerts
|

Critical Analysis of Stage IV Epithelial Ovarian Cancer Patients after Treatment with Neoadjuvant Chemotherapy followed by Cytoreductive Surgery and Hyperthermic Intraperitoneal Chemotherapy (CRS/HIPEC)

Abstract: Background. Cytoreductive surgery and hyperthermic intraperitoneal chemotherapy (CRS/HIPEC) after neoadjuvant chemotherapy (NACT) showed promise as initial treatment for stage IIIC (SIII) epithelial ovarian cancer (EOC); however, stage IV (SIV) outcomes are rarely reported. We assessed our experience and outcomes treating newly diagnosed SIV EOC with NACT plus CRS/HIPEC compared to SIII patients. Methods. Advanced EOC from 2015–2018 managed with NACT (carboplatin/paclitaxel) due to unresectable disease or poor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The relatively short follow-up period and inclusion of patients with stage IV disease may also have affected the DFS and OS rates. Some studies have shown similar results for stage IV patients following interval CRS with HIPEC [28,29]. Although statistical significance was not observed consistently, results for stage IV patients show a tendency for shorter DFS and OS.…”
Section: Strengths and Weaknessesmentioning
confidence: 87%
“…The relatively short follow-up period and inclusion of patients with stage IV disease may also have affected the DFS and OS rates. Some studies have shown similar results for stage IV patients following interval CRS with HIPEC [28,29]. Although statistical significance was not observed consistently, results for stage IV patients show a tendency for shorter DFS and OS.…”
Section: Strengths and Weaknessesmentioning
confidence: 87%
“…A study to investigate whether there is a cutoff that might suggest resectability would be useful and may then be of help in determining operability. The surgical PCI cutoff level for predicting completeness of CRS is controversial now, with reported cutoff values ranging from 15-25 [27,42,43]. Even so, this discovery bought a survival bene t to selecting CRS candidates and effectively avoided unnecessary aggressive surgery.…”
Section: Discussionmentioning
confidence: 99%